(untitled) (Biuletyn Kryminologiczny, 2021)
Article is a summary of two research projects realized in Department of Criminology the In- stitute of Law Studies of the Polish Academy of Sciences and in the Polish Institute of Justice. In the course of the projects were carried out two kind of research: court ﬁles analysis and individual semi-structured in-depth interviews. The research samples were: 397 juveniles from whom in 2014 the court issued decision on the application of the placement in a youth educa- tional centers or in a correctional facilities (case ﬁles research) and 40 educators from youth educational centers – YEC and correctional facilities – CF (qualitative research). The aim ofarticle is to present the results of these analysis. Artykuł jest podsumowaniem dwóch projektów badawczych zrealizowanych w Zakładzie Kryminologii Instytutu Nauk Prawnych Polskiej Akademii Nauk oraz Instytucie Wymiaru Sprawiedliwości. W ramach tych projektów zostały przeprowadzone dwa rodzaje badań: analiza akt spraw sądowych oraz indywidualne półustrukturyzowane wywiady pogłębione, na próbach: 397 akt spraw sądowych nieletnich, wobec których w 2014 roku sąd orzekł o umieszczeniu w młodzieżowym ośrodku wychowawczym lub w zakładzie poprawczym (badanie aktowe) oraz 40 wychowawców młodzieżowych ośrodków wychowawczych – MOW i zakładów poprawczych – ZP (badanie jakościowe). Celem artykułu jest sumaryczne przedstawienie wybranych wyników tychże badań.